The influence of the setup shape of a portable UWB system`s antennas in sport - Pino-Ortega, J.; Gantois, P.; Méndez, A.; Rico-González, M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2023)
Ultra-wide band (UWB) technology has become one of the most promising technologies of the future. It seems that the positioning of the antenna set influences the accuracy of the player`s performance. This study was aimed to assess the influence of two different antenna positioning system shapes: (i) octagonal installation and (ii) circular installation. A UWB technology was used to track a healthy and well-trained athlete`s (age: 38 years, mass: 76.34 kg, and height: 1.75 m) positioning. Overall, the data measured showed high accuracy in both shape setups in all trajectories assessed in static and dynamic conditions for all speed thresholds. However, the distance covered during jogging and sprinting showed poor accuracy for both shape setups. Moreover, the data measured showed high test-retest reliability and inter-device agreement in the static condition, regardless of the antenna setup shape. In conclusion, both the octagonal and circular antenna setup shape provided accurate data, but the measurement error associated within the setup shape seemed slightly different between the two systems.